2009
DOI: 10.1111/j.1651-2227.2009.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast does not prevent reactive airway disease in young children hospitalized for RSV bronchiolitis

Abstract: Treatment with montelukast after hospital admission for RSV bronchiolitis in children younger than 2 years of age did not reduce symptoms of cough and wheeze. We cannot exclude that a subgroup of children may, however, benefit from this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
(42 reference statements)
1
24
0
2
Order By: Relevance
“…Post hoc analyses of patients with persistent symptoms (SFD ≤ 30% over weeks 1-2) resulted in slight differences in % SDF over weeks 3 to 24 of 5.7 to 5.9 for montelukast (4 or 8 mg/day, respectively) versus placebo groups. A second study in 58 pediatric patients hospitalized with a first episode of RSV bronchiolitis seemed to confirm the conclusions of the previous study, and concluded that montelukast treatment did not reduce symptoms of cough and wheeze (Proesmans et al, 2009). During the three month trial period, no differences between the treatment and control groups were observed for symptom-free days and nights, and during the one year follow-up, no significant differences were observed in the number of exacerbations or time to first exacerbations, number of unscheduled visits and need to start inhaled steroids.…”
Section: Anti-inflammatory Agentssupporting
confidence: 74%
“…Post hoc analyses of patients with persistent symptoms (SFD ≤ 30% over weeks 1-2) resulted in slight differences in % SDF over weeks 3 to 24 of 5.7 to 5.9 for montelukast (4 or 8 mg/day, respectively) versus placebo groups. A second study in 58 pediatric patients hospitalized with a first episode of RSV bronchiolitis seemed to confirm the conclusions of the previous study, and concluded that montelukast treatment did not reduce symptoms of cough and wheeze (Proesmans et al, 2009). During the three month trial period, no differences between the treatment and control groups were observed for symptom-free days and nights, and during the one year follow-up, no significant differences were observed in the number of exacerbations or time to first exacerbations, number of unscheduled visits and need to start inhaled steroids.…”
Section: Anti-inflammatory Agentssupporting
confidence: 74%
“…For example, in an experimental rhinovirus infection model, montelukast had no effect upon rhinovirus-induced colds or asthma symptoms [88]. Montelukast has also been found not to affect respiratory symptoms after RSV bronchiolitis [89,90], or the incidence of upper respiratory tract infections [91].…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%
“…Likewise, no significant benefit of montelukast administered both at 4 and 20 weeks after the onset of respiratory symptoms was shown in a large study of infants with post respiratory syncytial virus (RSV) bronchiolitis [48]. A small RCT confirmed this result, showing that montelukast given for three months after hospital admission for RSV bronchiolitis did not reduce the respiratory symptoms during both the treatment and the follow up periods [49]. All these findings appear conflicting with the conclusions of one of the first studies of RSV bronchiolitis that showed that montelukast results in significant improvement of symptoms score and in decrease of nighttime symptoms and daytime cough [50].…”
Section: Scientific Evidences About Ltras In Preschool Childrenmentioning
confidence: 99%